The relationship between hormonal contraceptives, level of anxiety and emotional awareness: pilot project - Kecer, S; Pírek, O; Budínská, X; Světlák, M; Kon, E; Svačinová, J; Greplová, K; Valík, D; Svízela, V; Nováková, Z (Physiological research, 2024)
An important part of the side effects of combined oral contraceptives (COC) usage is its psychological impact, which includes mood changes, anxiousness and depression. The psychological impacts are expected to be caused by physiological fluctuations of sex hormone levels during the menstrual cycle; this cycling is, however, suppressed in COC users. In our study, we assessed the differences in emotional awareness and anxiousness between women long term users of anti-androgenic COC (AA) and women with no COC use in their medical history (C). We also searched for intraindividual differences by comparing the results of both groups for the follicular and luteal phase of their cycle. A total of 45 women aged 18 to 22 participated in this study. The respondents were given our battery of questionnaires at the beginning of their follicular phase - this battery included two State-Trait Anxiety Inventory questionnaires (STAI-I, STAI-II), as well as a Levels of Emotional Awareness Scale (LEAS) test. The respondents were given only STAI-I in their luteal phase. We also analyzed the hormonal profile of our respondents. Our results show a significant difference in the LEAS analysis, implying the possibility of altered emotional awareness in AA group. STAI-I and STAI-II analysis did not yield any significant results, showing that anxiety levels of COC users probably do not differ from the general female population. We therefore discovered lower emotional awareness in COC using women (AA). Key words LEAS, STAI, Combined oral contraceptives, Anxiety, Hormonal profile.
Keywords: dospělí; Emotions; Awareness; Female; Contraceptives, Oral, Combined; úzkost; Adult; mladý dospělý; ženské pohlaví; Menstrual Cycle; Adolescent; emoce; lidé; kontraceptiva orální hormonální; Pilot Projects; uvědomování si; pilotní projekty; Anxiety; Contraceptives, Oral, Hormonal; menstruační cyklus; Young Adult; mladiství; kontraceptiva orální kombinovaná; Humans